The Criteria of an Ideal Leader in QS. Al-Baqarah: 247: An Analysis of Ibn Kathir’s Tafsir and Its Relevance to Modern Leadership - Fuad Buntoro; Riswanto (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Leadership is a vital element in societal and governmental life. In Islam, the concept of leadership is firmly rooted, as reflected in the Qur'an, specifically in Surah Al-Baqarah, verse 247. This verse narrates the appointment of Talut as the leader of the Israelites, based on two primary qualifications: extensive knowledge and physical strength. This study aims to analyze the personality traits of a leader based on this verse, using the tafsir Al-Qur'anul Adzim by Imam Ibn Kathir as a primary reference. This research employs a qualitative-descriptive method with a library research approach. The primary sources used include Surah Al-Baqarah, verse 247, and the tafsir Al-Qur'anul Adzim by Imam Ibn Kathir. Secondary sources consist of books, journals, and articles related to the concept of leadership in Islam. The findings reveal that the main criteria for an ideal leader in the Islamic perspective include extensive knowledge encompassing both religious and general sciences, as well as physical readiness demonstrated through endurance, courage, and the ability to face challenges. Moreover, amanah (trustworthiness) emerges as a fundamental principle that includes responsibility, justice, and moral integrity. In the modern context, these values are highly relevant in the process of selecting and developing leaders to address the complexities of contemporary challenges. This study contributes to the leadership literature by highlighting that the Qur’an provides examples of criteria for selecting leaders and offers a new perspective on ideal leadership.